PENDIDIKAN LINGKUNGAN HIDUP MELALUI KEGIATAN BERSIH-BERSIH LINGKUNGAN DAN SOSIALISASI KLASIFIKASI SAMPAH DI DESA LURAGUNG LANDEUH - Tri Maulani Akbar; Rita Kusumah; Muhamad Ikbal Fauzie; Mahandari Desvita Salsabila; Reza Meisa Ningrum; Riva Nanda Wulandari; Sinta Mutiara (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Waste management problems and low public awareness of environmental cleanliness are serious challenges in many areas, including Luragung landeuh village. This community service activity aims to increase residents' awareness and understanding of the importance of maintaining environmental cleanliness and proper waste management through two main activities: environmental clean-up and socialization of waste classification. The implementation method uses a participatory approach involving 30 residents (10 male and 20 female) in RT 01 Luragung Landeuh village. This activity proves that community-based educational approaches are effective in improving public knowledge and behavior toward sustainable environmental management.